Micro-Sequential Coordination in Early Responses. Issue 4 (21st April 2021) - Deppermann, Arnulf; Schmidt, Axel
ABSTRACT: Our study deals with early bodily responses to directives (requests and instructions, i.e., second pair parts [SPPs]) produced before the first pair part (FPP) is complete. We show how early bodily SPPs build on the properties of an emerging FPP. Our focus is on the successive incremental coordination of components of the FPP with components of the SPP. We show different kinds of micro-sequential relationships between FPP and SPP: successive specification of the SPP building on the resources that the FPP makes available, the readjustment or repair of the SPP in response to the emerging FPP, and reflexive micro-sequential adaptions of the FPP to an early SPP. This article contributes to our understanding of the origins of projection in interaction and of the relationship between sequentially and simultaneity in interaction. Data are video-recordings from interaction in German.